Preparation process and formula of corrosion-resistant high-hardness multi-component composite coating on stainless steel surface
Through the multi-component coating formula and process of nickel-based powder and binder, the problems of long production cycle and high cost in the preparation of stainless steel surface coating are solved, and coating with high hardness, oxidation, corrosion resistance and wear resistance are achieved. The layer reduces powder waste and porosity, and improves the preparation efficiency and service life of the core surface coating.
Patent Information
- Application Number
- CN202411353919.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
The existing stainless steel surface coating preparation process has problems such as long production cycle, difficult worker operation, insufficient spraying, high porosity and a lot of powder waste. It is difficult to take into account both hardness, oxidation resistance, corrosion resistance and wear resistance, and the cost is high. Difficult to reduce.
Using a multi-composite coating formula of nickel-based powder and binder, the nickel-based powder content is 40-50% and the binder content is 50-60%. The coating is prepared by sandblasting treatment, ball milling, slurry hanging, drying and vacuum sintering processes. The layer controls the content and particle size of B, Cr, C, Fe and Ni, and combines the use of polyethylene glycol, sodium silicate and glycerone to improve the hardness and bonding properties of the coating.
Coatings with high hardness, oxidation resistance, corrosion resistance and wear resistance are prepared, which reduces production costs and powder waste, and improves the preparation efficiency and service life of the core surface coating.
Smart Images

Figure SMS_1 
Figure HDA0005063060710000011 
Figure HDA0005063060710000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of surface modification of metal materials, and particularly relates to a process for preparing a corrosion-resistant and high-hardness multi-component composite coating on a stainless steel surface and a coating formula thereof, and more specifically relates to a process for preparing a corrosion-resistant and high-hardness multi-component composite coating on a ball core surface and a coating formula thereof. Background Art
[0002] With the progress in petrochemical and other fields, the service environment of various stainless steel structural parts, such as ball valves and control valves, has become increasingly harsh. They face problems such as corrosion, high-temperature oxidation, and wear during use. The material failure caused by the above problems starts from the surface of the material. Therefore, surface engineering technology is an effective way to solve the above problems.
[0003] At present, the preparation of stainless steel surface coating generally adopts the method of thermal spraying nickel-based alloy powder + vacuum high-temperature sintering. The coating prepared by this method can basically meet the service requirements of stainless steel structural parts, but there are problems such as long production cycle and difficulty in operation for workers. For example, it is difficult to spray the inner wall of the stainless steel ball core, the spraying is not in place, the porosity after thermal spraying is too high, and there is a lot of powder waste. Therefore, how to reduce costs and increase efficiency has become the key to the development of stainless steel surface coating.
[0004] The coating prepared by the present invention can solve the above-mentioned problems existing in the coating prepared by the traditional process. At the same time, the prepared coating has excellent performance and achieves the effect of reducing costs and increasing efficiency. Summary of the invention
[0005] In view of the technical problems existing in the preparation process of stainless steel surface coating in the prior art, the purpose of the present invention is to provide a preparation process of stainless steel surface corrosion resistant high hardness multi-component composite coating and its coating formula. The coating formula of the present invention can take into account the hardness and anti-oxidation, corrosion resistance and wear resistance of the coating, and at the same time, the coating has the performance of low cost, high service life and service temperature.
[0006] The first aspect of the present invention provides a coating formula of a corrosion-resistant and high-hardness multi-component composite coating on a stainless steel surface, wherein the coating formula is composed of 40-50% nickel-based powder and 50-60% binder by weight percentage. The chemical composition of the nickel-based powder by weight percentage is: 15%-25% Cr, 2%-5% Fe, 6%-8% B, 0.5%-1% C, and the balance is Ni. The binder is composed of 1%-5% polyethylene glycol, 5%-10% sodium silicate, 1-5% acetone, and the balance is anhydrous ethanol by weight percentage.
[0007] In the above technical solution, the metal elements in the nickel-based powder are provided by metal element powders, wherein the purity of Cr, Fe, B, C and Ni powders are all analytically pure, and the powder particle size is controlled to be 100-300 meshes; the relative molecular weight of polyethylene glycol in the binder is 200-600, preferably PEG200 with a molecular weight of 200; the sodium silicate is a neutral sodium silicate solution, and its modulus is 1.5 The second aspect of the present invention provides a process for preparing a corrosion-resistant and high-hardness multi-component composite coating on a stainless steel surface, comprising the following steps: (1) Prepare the sample: sandblast the sample; (2) Preparation of slurry: weigh the raw materials according to the above coating formula, place them in a ball mill and grind them evenly, then take out the slurry for use. The viscosity of the slurry is 100-145 cP; the speed of the ball mill is 300-400 rpm, and the ball milling time is 1 hour.
[0008] (3) Slurry coating: Immerse the sample in the slurry, gently stir and rotate it, and take it out after 5-10 seconds. The appropriate slurry coating thickness is 0.8-1.2 mm.
[0009] (4) Drying: Place the coated sample in a drying oven and keep it at 300°C for 30-60 minutes to fully dry the coating and prevent bubbles during the sintering process.
[0010] (5) Sintering: Place the dried sample in a vacuum sintering furnace and maintain the vacuum degree at 10 -2 Pa, sinter in the furnace, heat up to 1050-1100℃ at a rate of 10-15℃ / min and keep warm for 20-30min; if the sintering speed is too fast, stress cracking of the coating will occur; if the sintering temperature is too low, the coating material will not melt fully; if the sintering temperature is too high, the performance of the substrate will be affected.
[0011] (6) Sampling: Take out the sample from the vacuum sintering furnace, air cool it, rinse it with running water, then clean it with alcohol, and then dry it to obtain a corrosion-resistant and high-hardness multi-component composite coating.
[0012] The nickel-based coating prepared by the present invention has a hardness of ≥55HRC, a coating thickness of ≥0.8 mm, and a few micropores and no cracks in the coating.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The coating formula of the invention can take into account the hardness and anti-oxidation, corrosion resistance and wear resistance of the coating. At the same time, the coating prepared by this formula has the performance of low cost, high service life and service temperature.
[0014] In the nickel-based powder provided by the present invention, the addition of B powder improves the high-temperature fluidity of the powder and avoids cracks in the coating during the sintering process. Excessive B will cause the mechanical properties of the coating to decrease, while insufficient B will affect the fluidity of the coating during sintering. In the present invention, the content of B is controlled to be 6-8%. The addition of Cr and C powders improves the hardness and wear resistance of the coating. Excessive addition of C will affect the toughness of the coating and easily cause ablation of C at high temperatures. On the contrary, if the addition amount is insufficient, the hardness of the coating will be affected. The addition of Cr powder improves the corrosion resistance of the coating. The addition of Fe powder is to improve the wettability with the stainless steel substrate.
[0015] In the binder provided by the present invention, the addition of polyethylene glycol and propylene glycol improves the adhesive force and powder carrying capacity of the binder, the addition of sodium silicate improves the high-temperature stability and high-temperature adhesiveness of the binder, and anhydrous ethanol plays a diluting role, thereby promoting the fluidity and expansibility of the slurry.
[0016] The coating preparation process of the present invention significantly improves the preparation efficiency of the core surface coating, improves the utilization efficiency of the powder, and reduces the production cost and product cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The surface morphology of the sample of Example 1 after immersion drying (left) and sintering (right); Figure 2 The surface morphology of the sample of Example 2 after immersion drying (left) and sintering (right); Figure 3 The surface morphology of the sample of Example 3 after immersion drying (left) and sintering (right); Figure 4 The surface morphology of the sample of Example 4 after immersion drying (left) and sintering (right); Figure 5 This is the surface morphology of the coating after sintering in Example 5; Figure 6 This is the surface morphology of the coating after sintering in Example 6; Figure 7 This is the surface morphology of the coating after sintering in Example 7; Figure 8 This is the interface structure of the coating prepared in Example 2. DETAILED DESCRIPTION
[0018] The present invention is described in detail below with reference to the embodiments.
[0019] The raw materials used in the following specific examples are as follows: Sample: The substrate used in the present invention is 304 stainless steel. The main components of 304 stainless steel include carbon (C) ≤ 0.08%, silicon (Si) ≤ 1.00%, manganese (Mn) ≤ 2.00%, phosphorus (P) ≤ 0.045%, sulfur (S) ≤ 0.03%, nickel (Ni) 8.0-10.5%, chromium (Cr) 18-20%, and the rest is mostly iron (Fe).
[0020] The purity of Cr powder, Fe powder, B powder, C powder and Ni powder are all analytically pure, and the powder particle size is 200-250 mesh. The polyethylene glycol used is PEG-200. The modulus of the sodium silicate solution is 1.5.
[0021] Other raw materials without special instructions are common commercial products. Example 1
[0022] (1) Prepare the sample: sandblast the sample to remove oil and oxides on the surface of the ball core and increase the surface roughness. The sandblasting pressure is 6-7MPa, and quartz sand with a particle size of 100-150 μm is used.
[0023] (2) Prepare slurry: According to weight percentage, the nickel-based powder composition is: 20% Cr powder, 4% Fe powder, 6% B powder, 0.8% C powder, and the balance is Ni powder; the binder composition is: 3% polyethylene glycol, 8% sodium silicate, 3% propylene glycol, and the rest is alcohol. The slurry composition is: 50% powder, 50% binder. Place the prepared slurry in a ball mill and grind it for 1 hour at a speed of 300 r / min, then take it out for use; (3) Slurry coating: immerse the sample (ball core) in the slurry, stir and rotate it slightly, and take it out after 5 seconds. The slurry coating thickness is 1 mm. (4) Drying: Place the sample after slurry coating in a drying oven and keep it at 300°C for 30 minutes to fully dry the coating and prevent bubbles during the sintering process; (5) Sintering: Place the dried sample in a vacuum sintering furnace and keep it at 1050°C for 20 min; (6) Sampling: Take out the sample from the vacuum sintering furnace, air cool it, rinse it with running water, then clean it with alcohol, and then dry it to obtain a multi-component composite coating.
[0024] Figure 1 The left picture shows the surface morphology of the sample after slurry drying, and the right picture shows the surface morphology of the coating after vacuum sintering. It can be seen from the figure that the coating is dense and uniform with fewer pores. Example 2
[0025] (1) Prepare the sample: same as in Example 1; (2) Prepare slurry: According to weight percentage, the nickel-based powder composition is: 20% Cr powder, 4% Fe powder, 7% B powder, 0.8% C powder, and the balance is Ni powder; the binder composition is: 3% polyethylene glycol, 8% sodium silicate, 3% propylene glycol, and the rest is alcohol. The slurry composition is: 50% powder, 50% binder. Place the prepared slurry in a ball mill and grind it for 1 hour at a ball mill speed of 350r / min, then take it out for use; (3) Slurry coating: immerse the sample (ball core) in the slurry, stir and rotate it slightly, and take it out after 8 seconds. The slurry coating thickness is 1 mm. (4) Drying: Place the sample after slurry coating in a drying oven and keep it at 300 °C for 45 min to fully dry the coating and prevent bubbles during sintering. (5) Sintering: Place the dried sample in a vacuum sintering furnace and keep it at 1080°C for 25 min; (6) Sampling: Take out the sample from the vacuum sintering furnace, air cool it, rinse it with running water, then clean it with alcohol, and then dry it to obtain a multi-component composite coating.
[0026] Figure 2 The left picture shows the surface morphology of the sample after slurry drying, and the right picture shows the surface morphology of the coating after vacuum sintering. It can be seen from the picture that the coating is dense and uniform with few pores. Figure 8 It can be seen that the coating and the substrate are completely metallurgically bonded. Example 3
[0027] (1) Prepare the sample: same as in Example 1; (2) Preparation of slurry: According to the weight percentage, the nickel-based powder composition is: 20% Cr powder, 4% Fe powder, 8% B powder, 0.8% C powder, and the balance is Ni powder; the binder composition is: 3% polyethylene glycol, 8% sodium silicate, 3% propylene glycol, and the rest is alcohol. The slurry composition is: 50% powder, 50% binder; place the prepared slurry in a ball mill and grind it for 1 hour at a speed of 400 rpm, then take it out for use; (3) Slurry coating: immerse the sample (ball core) in the slurry, stir and rotate it slightly, and take it out after 10 seconds. The slurry coating thickness is about 1 mm. (4) Drying: Place the sample after slurry coating in a drying oven and keep it at 300°C for 60 minutes to fully dry the coating and prevent bubbles during the sintering process; (5) Sintering: Place the dried sample in a vacuum sintering furnace and keep it at 1100°C for 30 min; (6) Sampling: Take out the sample from the vacuum sintering furnace, air cool it, rinse it with running water, then clean it with alcohol, and then dry it.
[0028] Figure 3 The left picture shows the surface morphology of the sample after slurry drying, and the right picture shows the surface morphology of the coating after vacuum sintering. It can be seen from the figure that the coating is dense and uniform with fewer pores. Example 4
[0029] The difference between Example 4 and Example 2 is that step (2) prepares the slurry: in terms of weight percentage, the nickel-based powder is composed of 20% Cr powder, 4% Fe powder, 7% B powder, 0.8% C powder, and the balance is Ni powder; the binder is composed of 1% polyethylene glycol, 8% sodium silicate, 5% acetone, and the rest is alcohol. The slurry is composed of 50% powder and 50% binder. The prepared slurry is placed in a ball mill and ground for 1 hour at a ball mill speed of 350 r / min. Other operations are the same as in Example 2.
[0030] Figure 4 The left picture shows the surface morphology of the sample after slurry drying, and the right picture shows the surface morphology of the coating after vacuum sintering. It can be seen from the figure that the coating is dense and uniform with fewer pores. Example 5
[0031] The difference between Example 5 and Example 2 is that step (2) prepares the slurry: in terms of weight percentage, the nickel-based powder is composed of 20% Cr powder, 4% Fe powder, 7% B powder, 0.8% C powder, and the balance is Ni powder; the binder is composed of 3% polyethylene glycol, 8% sodium silicate, and the rest is alcohol. The slurry is composed of 50% powder and 50% binder. The prepared slurry is placed in a ball mill and ground for 1 hour at a ball mill speed of 350 r / min. The other steps are the same as in Example 2.
[0032] The surface morphology of the coating after vacuum sintering is as follows Figure 5 As shown in the figure, it can be seen that the coating is cracked and has many pores. Example 6
[0033] The difference between Example 6 and Example 2 is that step (2) prepares the slurry: in terms of weight percentage, the nickel-based powder is composed of 20% Cr powder, 4% Fe powder, 0.8% C powder, and the balance is Ni powder; the binder is composed of 3% polyethylene glycol, 8% sodium silicate, 3% propylene glycol, and the rest is alcohol. The slurry is composed of 50% powder and 50% binder. The prepared slurry is placed in a ball mill and ground for 1 hour at a speed of 350 r / min, and then taken out for use. The other steps are the same as in Example 2.
[0034] The surface morphology of the coating after vacuum sintering is as follows Figure 6 As shown in the figure, it can be seen that the coating has more impurities and a large number of pores. Example 7
[0035] The coating slurry coating method of Example 7 is the same as that of Example 2, except that the vacuum sintering in step (5) is carried out at 1150°C for 20 minutes. The surface morphology of the coating after vacuum sintering is as follows: Figure 7 As shown in the figure, it can be seen that the coating is overburned and has a large number of pores.
[0036] The performance indicators and specific testing methods of the product of the present invention are as follows: The thickness, density and whether the cross section forms a metallurgical bond are all obtained by analyzing, observing and statistically analyzing the coating cross section under a scanning electron microscope; the hardness is the result of testing with a Rockwell hardness tester.
[0037] High temperature oxidation resistance: Use a muffle furnace to conduct oxidation tests, perform cross-section analysis, and study whether the coating has cracking, peeling and other failure behaviors, and compare it with the substrate. Experimental steps: 1. Sample preparation: Clean the coating and substrate samples to remove surface contaminants (such as grease, dust, etc.). Measure the dimensions of the samples and ensure that the initial state of each sample is recorded.
[0038] 2. Set up the muffle furnace: Turn on the muffle furnace, set the temperature to 1000°C, and set the heating rate (10°C / min) to ensure uniform temperature rise in the furnace.
[0039] 3. Place the sample: Place the sample in the center of the furnace.
[0040] 4. Oxidation treatment: Start heating and monitor the temperature changes in the furnace to ensure that the temperature rises steadily to 1000°C. Maintain oxidation treatment at 1000°C for 8 hours, during which the temperature is regularly monitored to ensure stability.
[0041] 5. Cooling: After the treatment, close the muffle furnace, take out the sample, and let it cool naturally to room temperature in the air to avoid thermal stress cracking of the sample due to rapid cooling.
[0042] The corrosion resistance was tested by using 4% NaCl solution. Experimental steps: 1. Sample preparation: Prepare the coating and substrate samples, ensure their surfaces are smooth and clean, and record the initial mass. The sample size should be consistent to ensure comparability of the experiments.
[0043] 2. Corrosion experiment setup: Prepare 4% NaCl solution, ensure it is evenly mixed and store at room temperature. Prepare a suitable container to hold the NaCl solution and ensure that the sample can be completely immersed.
[0044] 3. Immersion test: Immerse the sample completely in 4% NaCl solution and record the time when immersion starts. Set the immersion time to 48 hours and take out the sample after the time is up.
[0045] 4. Measure weight loss: After taking out the sample, wash it with deionized water to remove surface salt and gently dry it. Use a precision balance to measure the mass of each sample and record the mass change before and after immersion. Weight loss = initial mass − mass after immersion.
[0046] The nickel-based coating prepared by the present invention has a hardness of ≥55HRC, a coating thickness of ≥0.8mm, and a few micropores and no cracks. The specific performance test results of the coating are shown in Table 1 below.
[0047] Table 1 Coating performance test results
[0048] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A coating formula for a corrosion-resistant and high-hardness multi-component composite coating on a stainless steel surface, characterized in that: The coating formula is composed of 40-50% nickel-based powder and 50-60% binder by weight percentage; the chemical composition of the nickel-based powder by weight percentage is: 15%-25% Cr, 2%-5% Fe, 6%-8% B, 0.5%-1% C, and the balance is Ni; the binder is composed of 1%-5% polyethylene glycol, 5%-10% sodium silicate, 1-5% propylene glycol, and the balance is anhydrous ethanol.
2. The coating formula for the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 1 is characterized in that: The metal elements in the nickel-based powder are provided by metal element powders, wherein the purity of Cr, Fe, B, C and Ni powders are all analytically pure, and the powder particle size is controlled to be 100-300 meshes; the relative molecular weight of polyethylene glycol in the binder is 200; and the sodium silicate is a neutral sodium silicate solution, and its modulus is 1.
5.
3. A process for preparing a corrosion-resistant and high-hardness multi-component composite coating on a stainless steel surface, characterized in that: The steps include: (1) Prepare the sample: sandblast the sample; (2) Preparing slurry: weighing raw materials according to the coating formula of claim 1 or 2, grinding them evenly in a ball mill, and then taking out the slurry for later use; (3) Slurry: immerse the sample in the slurry, stir and rotate it slightly, and take it out after 5-10 seconds; (4) Drying: Place the coated sample in a drying oven to allow the coating to dry fully; (5) Sintering: Place the dried sample in a vacuum sintering furnace for vacuum sintering; (6) Sampling: Take out the sample from the vacuum sintering furnace, air cool it, clean it, and dry it to obtain a corrosion-resistant and high-hardness multi-component composite coating.
4. The preparation process of the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 3, characterized in that: The ball mill speed in step (2) is 300-400 rpm, and the ball milling time is 1 h.
5. The preparation process of the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 3, characterized in that: The viscosity of the slurry in step (2) is 100-145 cP.
6. The process for preparing the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 3, characterized in that: The slurry coating thickness in step (3) is 0.8-1.2 mm.
7. The process for preparing the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 3, characterized in that: The drying temperature in step (4) is 300°C and the drying time is 30-60 minutes.
8. The process for preparing the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 3, characterized in that: The vacuum sintering in step (5) is to increase the temperature to 1050-1100°C at a rate of 10-15°C / min and keep the temperature for 20-30 minutes.
9. The process for preparing the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 3, characterized in that: In the vacuum sintering described in step (5), the vacuum degree is maintained at 10 -2 Below Pa.
10. The process for preparing the corrosion-resistant and high-hardness multi-component composite coating on the surface of stainless steel according to claim 3, characterized in that: The cleaning described in step (6) is: air cooling, rinsing with running water, and then cleaning with alcohol.
